PORANG AGRIBUSINESS DEVELOPMENT STRATEGY (CASE STUDY: BINJAI CITY, BINJAI CITY DISTRICT, NORTH SUMATRA PROVINCE) - Simatupang, Donny Ivan Samuel; Pakpahan, Helena Tatcher; Haryanti, Heny (Journal of Agriculture, 2022)
This study aims to obtain information about internal and external factors affecting porang development and obtain porang development strategies in Binjai City. The data analysis method uses the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation) matrix, the IE (Internal-External) matrix, and the SWOT matrix. The results showed that the porang development strategy was an aggressive growth policy strategy by taking advantage of opportunities by using the strengths (SO Strategy) of the porang producers. Some strategies that can be applied are: (1) using social media and e-commerce as a promotional platform to increase customer interest by explaining the good quality of porang, how to cultivate plants that do not require special treatment, and how to process porang tubers into food, (2) the number of exporters and the need for exports are quite large, so the cultivation of porang plants has good potential and prospects in the future and has promising advantages.